Antibacterial effects of plants from lembang highland towards skin-infecting microorganisms - Anna Choirunnisa; Ita Nur Anisa; Dwi Yuliana Prasita; Suci Nar Vikasari (Science Midwifery, 2023)
Bacterial skin infection is a common infection in Indonesia. Staphylococcus aureus cause skin and soft tissue infections and Propionibacterium acnes causes acne (acnes vulgaris). Moringa oleifera, Piper betle, and Leucaena leucocephala leaves traditionally use as. This study aims is to evaluate antimicrobial activity of the ethanol extract of the leaves from Lembang highland against S. aureus and P. acnes. The extract of each leaves prepared using reflux in 50% ethanol and examination of antibacterial activity of the ethanol extract using the microdilution method in vitro. The results showed that the ethanol extracts of M.oleifera, P.betle, and L.leucocephala leaves had antibacterial activity against S. aureus and P. acnes with different minimum inhibitory concentrations. The greatest antibacterial activity against S.aureus was shown by the ethanol extract of moringa leaves (MIC = 1024 µg/ml), where the greatest antibacterial activity against P. acnes was possessed by the ethanol extract of betel leaves (MIC = 512 µg/ml).